Supply Chain Citizenship: Investigating the Antecedents of Customer Interorganizational Citizenship Behaviors. Issue 4 (25th November 2015) - Esper, Terry L.; Bradley, Randy V.; Thomas, Rodney; Thornton, LaDonna M.
Abstract : Research has consistently established the strategic importance of supply chain collaboration. As a result, interfirm behavioral dynamics and relationships have emerged as key topics for both the academic and practitioner communities. This paper explores an interpersonal exchange tactic that is inherent to many collaborative initiatives—interorganizational citizenship behaviors (ICBs). The study specifically investigates why retail customers in business‐to‐business exchange relationships would exhibit ICBs, and explores how they assess and respond to the ICBs of suppliers. Findings of the study suggest that customers generally interpret and value the various types of ICBs differently, resulting in differential effects regarding the supply chain performance and relational implications of the behavior. These results not only inform managerial practice but also provide future research opportunities in the area of ICBs and the broader realm of interpersonal supply chain dynamics.